MICROBIOLOGICAL ANALYSIS IN THE BOTTLES USED IN A DAY CARE CENTER IN THE MUNICIPAL SCHOOL SYSTEM IN THE CITY OF ARARA - Bivar Cândido, Patrícia; Beatriz Varelo Albino, Ana; Eduardo Adelino, José (Health and Society, 2023)
Baby bottles have become essential tools to aid infant feeding, however, they are objects of easy contamination by microorganisms that can engender pathogens arising mainly from bacteria. Escherichia coli, Citrobacter, Enterobacter and Klebsiella are bacteria that belong to the coliform group and can trigger gastrointestinal disorders, characterized by watery diarrhea, urinary tract infection, pneumonia and meningitis. Failure to properly disinfect baby bottles exposes children to the risk of infection by these agents. The objective of the present work was to carry out a microbiological evaluation for the possible detection of thermotolerant coliforms (E. Coli) in baby bottles used in a public day care center in the city of Arara - PB, where the samples were collected, conditioned in suitable containers and transferred to the laboratory for analysis of the COLItest® kit. Twenty bottles shared by the children were analyzed, which revealed the presence of total coliforms in 85%, among which the presence of Escherichia coli was detected in 23.5%, and only 15% of the total were negative for both strains. The results point to the hypothesis that there are flaws in the hygiene of bottles and the hands of the professionals who handle them, and it is important to instruct them about Good Food Handling Practices (BP).